Extracorporeal Membrane Oxygenation Appropriateness: An Interdisciplinary Consensus-Based Approach. (March 2019) - Nurok, Michael; Warsh, Jonathan; Griner, Todd; Kharabi, Mayumi; Castongia, Joseph; Overbeck, Cali; Krueger, Lisa; Coleman, Bernice; Ramzy, Danny; Chung, Joshua; Chan, Alice; Ley, Eric; et al.
Abstract : We describe a quality improvement initiative aimed at achieving interdisciplinary consensus about the appropriate delivery of extracorporeal membrane oxygenation (ECMO). Interdisciplinary rounds were implemented for all patients on ECMO and addressed whether care was consistent with a patient's minimally acceptable outcome, maximally acceptable burden, and relative likelihood of achieving either. The rounding process was associated with decreased days on venoarterial ECMO, from a median of 6 days in 2014 (first quartile [Q1]–third quartile [Q3], 3–10) to 5 days in 2015 (Q1–Q3, 2.5–8) and in 2016 (Q1–Q3, 1–8). Our statistical methods do not allow us to conclude that this change was due to our intervention, and it is possible that the observed decreases would have occurred whether or not the rounding process was implemented.